“Ciberneretica” simondoniana - Sunseri, Francesca (Philosophy Kitchen - Rivista di filosofia contemporanea, 2023)
This paper analyses the reception of Norbert Wiener’s cybernetics in France with particular attention to the perspective proposed by Gilbert Simondon. The debate that has emerged since the 1950s among the philosophers of the so-called French Theory opens up the possibility of speaking of a revised cybernetics on the basis of the need to go beyond the structural analogy between living being and machine. The present paper investigates the relationship between Simondon and cybernetics by considering his 1953 manuscript, his two doctoral theses and his speech at the Royaumont conference in 1962. It also focuses on the concept of ecceità that Simondon uses in order to speak from the qualitative side of information and to propose an ontological perspective in which it is that which goes beyond the limits of Aristotelian hylomorphism.